Climate and anthropogenic drivers of changes in abundance of C4 annuals and perennials in grasslands on the Mongolian Plateau. Issue 2 (20th June 2022) - Yang, Hao; Auerswald, Karl; Gong, Xiaoying; Schnyder, Hans; Bai, Yongfei
Abstract: Background: C4 plants have increased substantially during the past several decades in the grasslands of the Mongolian Plateau due to regional warming. Here, we explore how the patterns of abundances of C4 annuals and C4 perennials change over space and time. Methods: A total of 280 sites with C4 plants were surveyed in four types of grasslands in 9 years. The relative biomasses of C4 plants (PC4 ), C4 annuals (PA4 ), and C4 perennials (PP4 ) were calculated. Structural equation modeling was used to analyze the drivers of changes in PA4 and PP4 . Results: At the regional scale, PA4 on average was 11% (±19%, SD) and PP4 was 13% (±19%, SD). Spatially, C4 annuals dominated the C4 communities within an east–west belt region along 44° N and tended to spread toward northern latitudes (about 0.5°) and higher altitudes in the east mountainous areas. The abundance of C4 annuals decreased, while that of C4 perennials increased. The patterns of C4 annuals and C4 perennials were mainly controlled by temperature, growing season precipitation, and dynamics between the two life forms. Conclusions: C4 annuals exhibited competitive advantages in normal and wet years, while C4 perennials had competitive advantages in dry years. Grazing as a main human disturbance increased C4 annuals, but had no significant effect on C4 perennials. Abstract : The spatiotemporal patterns of C4 annuals and C4 perennials were mainly controlled by temperature, growing season precipitation, and dynamics between the two life forms. Grazing as a main human disturbance increased C4 annuals, but had no effect on C4 perennials.